Discovering Words in Fluent Speech: The Contribution of Two Kinds of Statistical Information - Thiessen, Erik D.; Erickson, Lucy C. (Frontiers in Psychology, 2013)
To efficiently segment fluent speech, infants must discover the predominant phonological form of words in the native language. In English, for example, content words typically begin with a stressed syllable. To discover this regularity, infants need to identify a set of words. We propose that statistical learning plays two roles in this process. First, it provides a cue that allows infants to segment words from fluent speech, even without language-specific phonological knowledge. Second, once infants have identified a set of lexical forms, they can learn from the distribution of acoustic features across those word forms. The current experiments demonstrate both processes are available to 5-month-old infants. This is an earlier age than prior demonstration of sensitivity to statistical structure in speech, and consistent with theoretical accounts that claim statistical learning plays a role in helping infants to adapt to the structure of their native language from very early in life.